Factors Contributing to the Success of Blended Learning in an EFL Learning Context - Challob, Ala'a Ismael; Eid, Omar Sabah (Universitas Pahlawan Tuanku Tambusai, 2025)
Blended learning has become an important trend in the teaching and learning of the English language. Although numerous studies have investigated its effectiveness, the specific factors contributing to its success remain unclear and somewhat overlooked. This study aims to identify the key factors that support the successful implementation of blended learning in the university EFL context in Iraq. Using a quantitative descriptive research design, a questionnaire covering four domains was administered to a sample of fifty-five fourth-year Iraqi EFL students from the English Department at the University of Anbar. The data was analyzed using SPSS to determine means and standard deviations. The findings revealed that institutional factors, teacher-related factors, psychological factors, and student-related factors, respectively, play significant roles in the effectiveness of blended learning. The study concludes that combining traditional education with modern technologies can enhance learning outcomes in English as a foreign language at the university level in Iraq.